Comparative assessment of the effectiveness of situational leadership in theological seminaries of the Igreja Presbiteriana do Brasil-IPB: measuring leadership in the directors' self-perception - Araújo, Paulo César Diniz de (2024)
This article carried out a Comparative Assessment of the Effectiveness of Situational Leadership in Theological Seminaries of the Presbyterian Church of Brazil-IPB: Measurement of the directors' self-perception. This work also achieves its specific objectives by carrying out a bibliographical research on the topic of Leadership, specifically highlighting Situational Leadership, by Hersey and Blanchard (1986); Soon after, he applied the Situational Leadership form (flexibility and adaptability of styles), by Hersey and Blanchard (1986), by filling out the LEAD form – Leadership Effectiveness and Adaptability Description, together with the 10 directors of the IPB theological Presbyterian seminaries; Soon after, the data collected was tabulated using the Situational Leadership form LEAD – Leadership Effectiveness and Adaptability Description, by Hersey and Blanchard (1986), according to the appendix of this work. And finally, a comparative assessment of the effectiveness of Situational Leadership, by Hersey and Blanchard (1986), was carried out among the leaders of the Theological Seminaries of the Presbyterian Church of Brazil-IPB. The research developed on the Comparative Assessment of the Effectiveness of Situational Leadership in the Theological Seminars of the Presbyterian Church of Brazil-IPB, allowed the following conclusions: Regarding the instrument applied, the positioning of column I - Amplitude of Style, of the LEAD Instrument (Leadership) was identified. Effectiveness and Adaptability Description. The following conclusions were reached: the style most used by the directors of the IPB Presbyterian Seminars, in column I of Amplitude of Styles, was Style 2 (E2) that of Persuading with 72 points; The second style most used by directors of IPB Presbyterian Seminaries, in column I of Breadth of Styles was Style 3 (E3) of Sharing with 28 points; and the third most used style by directors of IPB Presbyterian Seminaries, in column I of Breadth of Styles, Style 1 (E1) was Determine with 15 points. As for the instrument applied, the positioning of column II - Style Adaptability, of the LEAD Instrument (Leadership Effectiveness and Adaptability Description) was identified. This monograph helped to answer the research question: what is the degree of Effectiveness of the Situational Leadership of the directors in the Theological Seminaries of the Presbyterian Church of Brazil-IPB, with the measurement of leadership in the directors' self-perception? Which concluded, proving the hypothesis, that the effectiveness of the directors of Presbyterian seminaries, who responded on a self-perception, that the overall effectiveness was average, divided into three groups, as described in the research. Also, that there are different levels of effectiveness of situational leadership spread across IPB seminars in the country. In other words, the Practice and Effectiveness of situational leadership in the 10 IPB seminars is not uniform and, sometimes, this is understood and accepted by the respective leaders.